Probe-type ultrasound-assisted immersion freezing of meat, study of selected quality factors and taguchi-based process optimization - Hamed Sardari; Reza Alimardani; Mahmoud Soltani Firouz; Soleiman Hosseinpour (Applied Food Research, 2025)
This paper evaluated the impact of refrigerator freezing (RF), immersion freezing (IF) and ultrasound-assisted immersion freezing (UIF) at different power levels (50, 100, 125, 150, 175, 200, 300, and 400 W) on the physicochemical properties of meats in full-duty-cycle (FDC) and half-duty-cycle (HDC). The mechanism of the effect of the mode of ultrasound field (pulsed or continuous) on the freezing process of meat was elucidated. The optimum processing parameters were selected by applying the Taguchi methodology which revealed that optimum freezing time and quality factors were achievable with ultrasound power of 125 W and duty cycle of 50 %. Compared to RF and IF, the UIF samples had lower thawing and cooking loss and remarkably reduced freezing times, especially in the HDC. Scanning electron microscope (SEM) images confirmed the significant effect of ultrasonication to the formation of ice crystals, where HDC-UIF-125 illustrated the best result among other treatments by generating uniform ice crystals. Furthermore, browning index (BI) and total color difference (ΔE) were obtained using L*, a* and b* color channel, which proved the significant effect of ultrasonication, in comparison to the conventional method, especially in HDC-UIF-125 where BI and ΔE were minimal and L*, a* and b* were the closest to the color properties of fresh meat. Overall, the appropriate ultrasonic power had a positive effect on maintaining the quality of frozen meat and improving appearance characteristics.